2022
DOI: 10.46729/ijstm.v3i1.402
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review: Delone and Mclean Model using VOSViewer on Google Scholar Database Case Year 2010-2020

Abstract: This study aims to examine the development of the Delone and Mclean information system success model. This research was conducted to determine: (1) a map of the development of the number of publications on the Delone and Mclean model; (2) find out which scientific articles have the highest number of citations; (3) knowing the development map of scientific publications based on keywords. The data sources used in this study are scientific articles in the Google Scholar database with the keywords Delone and Mclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A meta-analytic evaluation of pairwise relationships among variables of the D&M ISSM was performed in 2009 by Petter and McLean [25], and the following associations were most firmly established when the number of studies reporting the association (minimum 9-31) and the meta-analytic effect size (.48 -.65) were used as criterion for a high level of relationship: user satisfaction → IU (9studies/.65), net benefits → IU (14 studies/.55), system quality → user satisfaction (17 studies/.54), INFQ → user satisfaction (10 studies/.53), user satisfaction → net benefits (31 studies/.52), SYSQ → IU (12 studies/.48). The fact that the D&M ISSM persists to attract the interest of researchers has recently been confirmed by Rahayu and Setiyani [26], who found that since 2010, the number of papers using this model published annually has been continuously increasing.…”
Section: Delone and Mclean Information Systems Success Modelmentioning
confidence: 85%
“…A meta-analytic evaluation of pairwise relationships among variables of the D&M ISSM was performed in 2009 by Petter and McLean [25], and the following associations were most firmly established when the number of studies reporting the association (minimum 9-31) and the meta-analytic effect size (.48 -.65) were used as criterion for a high level of relationship: user satisfaction → IU (9studies/.65), net benefits → IU (14 studies/.55), system quality → user satisfaction (17 studies/.54), INFQ → user satisfaction (10 studies/.53), user satisfaction → net benefits (31 studies/.52), SYSQ → IU (12 studies/.48). The fact that the D&M ISSM persists to attract the interest of researchers has recently been confirmed by Rahayu and Setiyani [26], who found that since 2010, the number of papers using this model published annually has been continuously increasing.…”
Section: Delone and Mclean Information Systems Success Modelmentioning
confidence: 85%
“…Step 4: Data Analysis The data that had been organized with Open Refine will be applied in Vos Viewer, an application that can be used as open source; this is the product of the Centre for Science and Technologies Studies, Leiden University, Netherlands, an application that can construct and visualize bibliometric system just like journal, title, author, writer, publication, etc. (Dhian Nur Rahayu & Lila Setiyani, 2022). Vos Viewer can also map many kinds of bibliometric analysis, and resulted from a sophisticated visualization with visual labelling (Nurul Zakiyyah & Winoto, 2022).…”
Section: Methodsmentioning
confidence: 99%